Precision Polymer Engineering's sealing material plays a key role in Venice's flood prevention measures. Issue 7 (July 2019) - Atkinson, Simon
Abstract : A sealing material developed by Precision Polymer Engineering Ltd (PPE) of Blackburn, UK, is playing a key role in flood prevention measures off the coast of Italy. This focus article provides a glimpse into how technology from the company – which designs, develops and manufactures high-performance moulded rubber seals, rubber gaskets and elastomer components for industries around the world – is being used in a series of massive flood gates that has been installed to protect the city of Venice and the Venetian Lagoon from flooding.